Identification of slot discharges in rotating machine insulation system using variable frequency PD measurement. Issue 3 (1st September 2018) - Nair, Ramesh P.; B. Vishwanath, Sumangala; B. Rao, Nageshwar
Abstract : Slot discharge studies are very important from the insulation diagnosis perspective. Further in practice, testing of rotating machines with power frequency requires sources which are quite bulky and costly. Instead if the diagnosis is carried out at lower frequencies (<50 Hz), the size and cost of the test source can be reduced significantly. Therefore, it is important to know whether the study at low frequencies can be considered equivalent to study at power frequency. Hence, in this study, a slot discharge phenomenon occurring in a rotating machine insulation system was investigated experimentally at different frequencies (50, 10, 1 and 0.1 Hz). Slot discharges are known to have a distinct phase resolved partial discharge pattern for power frequency (50/60 Hz) excitation. These distinct patterns are useful in identifying the presence of slot discharge activity in rotating machines. Slot discharges were created on a 6.6 kV mica‐epoxy stator coil and the slot discharge characteristics measured at different frequencies are compared. Slot discharge measurements were repeated by varying the air gap between the insulation surface and grounded steel plate. The changes in slot discharge characteristics due to the increase in air gap were found similar at all frequencies. The comparison suggests that the identification of slot discharge is also possible from the partial discharge (PD) measurement at low frequencies.